«…the only thing left to eat is the truth». Image, Text and Artivist Critique in Shaun Tan’s "Tales from the Inner City" (Connessioni remote. Artivismo_Teatro_Tecnologia, 2021)
The work of Australian visual artist and writer Shaun Tan is characterized by productive fusions of text and image powering his politically charged artistic practice – a practice of artivist intervention to mobilize what Neumann and Rippl (2020) call «Verbal-visual configurations». This article explores the forms and functions of verbal-visual configurations in Tan’s work. I close-read two episodes from his recent visual narrative Tales from the Inner City (2018), with a particular focus on how «intermedial strategies» are employed to address pressing issues in the so-called Anthropocene: power relations, anthropocentrism, and human exceptionalism. I suggest that Tales from the Inner City enables a productive argument about textual-visual resistance repertoires, and I analyze the “intermedial aesthetics” sustaining this artivist intervention.
Keywords: Intermediality; Environmentalism; Anthropocene; Visual Narratives; Visual-Literary Activism; Artivism